Further Evidence That the Effects of Repetition on Subjective Time Depend on Repetition Probability - Skylark, William J.; Gheorghiu, Ana I. (Frontiers in Psychology, 2017)
Repeated stimuli typically have shorter apparent duration than novel stimuli. Most explanations for this effect have attributed it to the repeated stimuli being more expected or predictable than the novel items, but an emerging body of work suggests that repetition and expectation exert distinct effects on time perception. The present experiment replicated a recent study in which the probability of repetition was varied between blocks of trials. As in the previous work, the repetition effect was smaller when repeats were common (and therefore more expected) than when they were rare. These results add to growing evidence that, contrary to traditional accounts, expectation increases apparent duration whereas repetition compresses subjective time, perhaps via a low-level process like adaptation. These opposing processes can be seen as instances of a more general “processing principle”, according to which subjective time is a function of the perceptual strength of the stimulus representation, and therefore depends on a confluence of “bottom-up” and “top-down” variables.